The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1074/jbc.m117.816298
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and essentiality of fumarate hydratase

Abstract: Plasmodium falciparum (Pf), the causative agent of malaria, has an iron-sulfur cluster-containing class I fumarate hydratase (FH) that catalyzes the interconversion of fumarate to malate, a wellknown reaction in the tricarboxylic acid cycle. In humans, the same reaction is catalyzed by class II FH that has no sequence or structural homology with the class I enzyme from Plasmodium. Fumarate is generated in large quantities in the parasite as a byproduct of AMP synthesis and is converted to malate by FH and then… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
(69 reference statements)
1
14
0
Order By: Relevance
“…Ferredoxin (PF3D7_1214600) is expected to be essential (18), but its main role is to provide electrons for the ISC pathway (39). Class I fumarate hydratase (PF3D7_0927300), which functions in the TCA cycle but may also contribute to purine scavenging, was refractory to disruption in P. falciparum (7) but successfully deleted in P. berghei in a mouse strain-dependent manner (40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferredoxin (PF3D7_1214600) is expected to be essential (18), but its main role is to provide electrons for the ISC pathway (39). Class I fumarate hydratase (PF3D7_0927300), which functions in the TCA cycle but may also contribute to purine scavenging, was refractory to disruption in P. falciparum (7) but successfully deleted in P. berghei in a mouse strain-dependent manner (40).…”
Section: Resultsmentioning
confidence: 99%
“…Ferredoxin (PF3D7_1214600) is expected to be essential (19), but its main role is to provide electrons for the ISC pathway (43). Class I fumarate hydratase (PF3D7_0927300), which functions in the TCA cycle but may also contribute to purine scavenging, was refractory to disruption in P. falciparum (8) but successfully deleted in P. berghei in a mouse strain-dependent manner (44). The Rieske protein (PF3D7_1439400), which is an essential component of ETC complex III (45), is the only known mitochondrial Fe-S cluster protein that has an unequivocally essential function apart from the ISC pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was shown that 2-thiomalate is also a micromolar inhibitor of class I FHs from parasites Trypanosoma cruzi and Plasmodium falciparum but does not inhibit human FH. 10 , 11 To our knowledge, 2-thiomalate is the first selective small molecule inhibitor of class I FHs, and here we show that this selectivity arises from the binding of the inhibitor to the class I FH catalytic [4Fe-4S] cluster; the human class II FH does not utilize a [4Fe-4S] cluster. In addition, LmFH-1 and LmFH-2 structures show high structural similarity, indicating that inhibitors of one isoform are likely to inhibit the other isoform.…”
mentioning
confidence: 58%
“…2-Thiomalate has also been identified as a micromolar competitive inhibitor of class I FHs from Trypanosoma cruzi ( K i, malate = 4.2 ± 0.5 μM for cytosolic isoform; K i, malate = 1.3 ± 0.1 μM for mitochondrial isoform) and Plasmodium falciparum ( K i = 0.32 ± 0.03 μM for S -malate; K i = 0.55 ± 0.05 μM for fumarate) but does not inhibit class II human FH. 10 , 11 To our knowledge, 2-thiomalate is the first selective inhibitor of class I FHs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation